2021
DOI: 10.1177/11206721211070305
|View full text |Cite
|
Sign up to set email alerts
|

Expression of SCO1 and SCO2 after form-deprivation myopia in Guinea pigs

Abstract: Purpose The retina is a highly energy-consuming tissue associated with visual development, and the reduced quality of retinal imaging can be related to myopia. Synthesis of cytochrome c oxidase 1 ( SCO1) and synthesis of cytochrome c oxidase 2 ( SCO2) are involved in ATP (adenosine triphosphate) synthesis and energy metabolism. This study aimed to observe the morphologic changes and investigate the expression of SCO1 and SCO2 induced by form-deprivation myopia (FDM) in the retina and sclera of guinea pigs. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Cytochrome C was, however, upregulated in LIM while downregulated in FDM. In a previous study with an FDM model of guinea pigs, both protein and mRNA expression levels of cytochrome C protein (SCO1 and SCO2) were found to be considerably lower in the FDM group [43]. The second analysis in Figure 6B represented relative expression levels of all five complex genes.…”
Section: Oxidative Phosphorylation Revealed Specific Alterationsmentioning
confidence: 89%
“…Cytochrome C was, however, upregulated in LIM while downregulated in FDM. In a previous study with an FDM model of guinea pigs, both protein and mRNA expression levels of cytochrome C protein (SCO1 and SCO2) were found to be considerably lower in the FDM group [43]. The second analysis in Figure 6B represented relative expression levels of all five complex genes.…”
Section: Oxidative Phosphorylation Revealed Specific Alterationsmentioning
confidence: 89%
“…Several genes were reported to be associated with HM, but classical myopia characteristics such as refractive error change and prolonged axial length were not observed in gene mutant animal models [22,54]. The form deprivation myopia (FDM) was a classical approach to induce a high myopia model and it was successfully established in different animal species, including monkeys, mice, chickens, tree shrews, guinea pigs, and rats [44,[55][56][57][58][59][60]]. To amplify the potential impact of Timp4 knockdown on ocular development, we established a form deprivation model on the three-week-old rats of three genotypes, referring to the previously reported form deprivation models of chicken and rats [45,61] (Figure A2B).…”
Section: Determination Of Ocular Components Under Extra Pressure From...mentioning
confidence: 99%
“…Recent studies have shown that RGCs may be involved in the occurrence and development of myopia. Clinical studies and animal experiments have confirmed that myopia can cause a decrease in the number of RGCs [ 19 , 20 ]. Early-onset high myopia can cause abnormal axonal projection of RGCs [ 21 ].…”
Section: Introductionmentioning
confidence: 99%